The impact of a student death doula service-learning experience in palliative care settings on nursing students: A pilot mixed-methods study. - Yoong, Si Qi; Wang, Wenru; Seah, Alvin Chuen Wei; Chao, Felicia Fang Ting; Kumar, Nivetha; Gan, Joanne Oon Nee; Schmidt, Laura Tham; Hong, Jingfang; Zhang, Hui (Death Studies, 2025)
Through a mixed-methods approach (randomized controlled trial and thematic analysis of pre and post-service-learning reflections), this study evaluated the impact of a student death doula service-learning experience on nursing students' palliative competencies and learning experiences. The intervention group underwent a 2-day student death doula training workshop followed by a 6-month service-learning experience, while the control group received standard palliative care education. Attitudes toward the care of the dying significantly improved for the intervention group but not for compassion competence and palliative care knowledge. Six themes were developed: (1) Motivations for being a student death doula, (2) Improved perceptions of palliative care patients, (3) Perceptions of a good death, (4) Confidence in caring for palliative care patients, (5) Understanding the multifaceted nature of palliative care, and (6) Joys and challenges during service-learning. Service-learning helped students to understand palliative care patients and acquire confidence in engaging with them.